A Bcl11bN797K variant isolated from an immunodeficient patient inhibits early thymocyte development in mice - Matsumoto, Kazuaki; Okuyama, Kazuki; Sidwell, Tom; Yamashita, Motoi; Endo, Takaho; Satoh-Takayama, Naoko; Ohno, Hiroshi; Morio, Tomohiro; Rothenberg, Ellen V.; Taniuchi, Ichiro (Frontiers in Immunology, 2024)
BCL11B is a transcription factor with six C2H2-type zinc-finger domains. Studies in mice have shown that Bcl11b plays essential roles in T cell development. Several germline heterozygous BCL11B variants have been identified in human patients with inborn errors of immunity (IEI) patients.Among these, two de novo mis-sense variants cause asparagine (N) to lysine (K) replacement in distinct zinc-finger domains, BCL11B N441K and BCL11B N807K . To elucidate the pathogenesis of the BCL11B N807K variant, we generated a mouse model of BCL11B N807K by inserting the corresponding mutation, Bcl11b N797K , into the mouse genome. In Bcl11b +/N797K mice, the proportion of immature CD4 -CD8 + single-positive thymocytes was increased, and the development of invariant natural killer cells was severely inhibited in a T-cell-intrinsic manner.Under competitive conditions, gdT cell development was outcompeted by control cells.Bcl11b N797K/N797K mice died within one day of birth. Recipient mice reconstituted with Bcl11b N797K/N797K fetal liver cells nearly lacked CD4 + CD8 + double-positive thymocytes, which was consistent with the lack of their emergence in culture from Bcl11b N797K/N797K fetal liver progenitors.Interestingly, Bcl11b N797K/N797K progenitors gave rise to aberrant c-Kit + and CD44 + cells both in vivo and in vitro. The increase in the proportion of immature CD8 single-positive thymocytes in the Bcl11b N797K mutants is caused, in part, by the inefficient activation of the Cd4 gene due to the attenuated function of the two Cd4 enhancers via distinct mechanisms. Therefore, we conclude that immunodeficient patient-derived Bcl11b N797K mutant mice elucidated a novel role for Bcl11b in driving the appropriate transition of CD4 -CD8 -into CD4 + CD8 + thymocytes.